Race and crime - Gabbidon, Shaun L. (Sage, 2025)
"Written by two of the most prominent criminologists in the field, Race and Crime, 6th Edition takes an incisive look at the intersection of race and ethnicity and the criminal justice system. A thought-provoking discussion of contemporary issues uniquely balances the historical context and modern data and research to offer students a panoramic perspective on race and crime. Accessible and reader friendly, this comprehensive text shows students how race and ethnicity have mattered and continue to matter in all aspects of the administration of justice. Features and Benefits: Historical details and contemporary information are presented in every chapter to help students develop a comprehensive understanding and make more informed decision in regards to race and crime. An issues approach focuses on several contemporary challenges such as immigration and crime, hate crimes, racial profiling, sentencing disparities, minority female delinquency, and wrongful convictions. Coverage of major racial and ethnic groups in the United States ensures students are receiving the most current data and research available on groups of individuals. Internet exercises at the end of each chapter give students the opportunity to further their knowledge and understanding of race and crime"--